Between‐ and within‐species trait variability and the assembly of sapling communities in forest patches. (1st September 2014) - Carlucci, Marcos B.; Debastiani, Vanderlei J.; Pillar, Valério D.; Duarte, Leandro D. S.; de Bello, Francesco
Abstract Questions What is the magnitude of between‐species trait variability (BSV) and within‐species trait variability (WSV) of specific leaf area (SLA) in a sapling meta‐community? To what extent do species turnover and WSV influence community‐level mean trait responses to an environmental gradient and trait spread patterns across this gradient? What is the role of WSV for mean plant responses to environmental variation and niche partitioning in structuring sapling communities? Location Forest patches within a native grassland matrix in southern Brazil. Methods We recorded saplings in community plots across a canopy openness gradient in forest patches and described each of the 1129 individuals using SLA. First, we partitioned trait variation into BSV and WSV irrespective of co‐occurrence in plots. Then, using the community data, we partitioned the total variation of community‐weighted trait means (CWM) and Rao's functional diversity (FD) into components explained by canopy openness, species turnover and WSV. We also partitioned the effects of WSV between and within plots on FD. Finally, we explored the responses of CWM and FD to the gradient using the whole trait variability, only BSV or only WSV. Results Specific leaf area presented a substantial proportion of variation within species (37%), although it varied more between species (63%). Species turnover and WSV explained 48% and 19% of the variation in CWM across the gradient, respectively. Species turnover and WSV explained 51% and 45% of the variation in FD across the gradient, respectively. SLA varied within species more along the gradient than within communities. Within‐species variability enhanced shifts in CWM and FD across the gradient. Canopy openness significantly predicted CWM at all levels, and FD at all but the within‐species level. Conclusions Plastic responses of species mirrored the average response of communities to the environmental gradient. Within‐species trait variability enhanced the mean plant responses to environmental variation as well as niche partitioning, and was especially important in enabling species to establish in a wider portion of the environmental gradient. Our study provides new evidence that population‐level phenomena matter for community assembly.